The spectrum of neuroradiological features in Menkes disease: Widening of the cerebral venous sinuses - Bernhard, Matthias K.; Merkenschlager, Andreas; Mayer, Thomas; Muntau, Ania; Pfluger, Thomas (Journal of Pediatric Neuroradiology, 2012)
Menkes disease, an inherited disorder of copper transport, shows a spectrum of different neuroradiological findings. Diffuse brain atrophy, deficient myelination, and subdural hematoma/hygroma were described. Anomalies of the cerebral arteries with elongation and tortuosity are known. We report the neuroradiological follow up of a patient suffering from Menkes disease confirmed by the identification of a deletion of ATP 7A gene. Ultrasound scanning at the age of two months demonstrated normal brain morphology. One month later, magnetic resonance imaging (MRI) showed vermian hypoplasia, brain atrophy and retarded myelination. Marked widening of cerebral venous sinuses in conventional angiography and in magnetic resonance venography was detected and led to arterial cerebral angiography, which did not disclose an arteriovenous fistula. Despite parenteral copper therapy, on MRI follow up seven months later, extra-axial blood and hygroma were visible and the signs of cerebral atrophy and myelination deficit were more pronounced. In Menkes disease, neuroradiological anomalies can occur early and progress rapidly despite copper therapy. When evaluating magnetic resonance angiography results in neurodegenerative diseases, Menkes disease should be suspected not just when cerebral arterial anomalies are demonstrated. Widening of the cerebral venous sinuses might be caused by secondary to brain atrophy or involvement of the vein walls.
Keywords: Neurodegenerative diseases; copper uptake; MRI; cerebral vessels; developmental delay